Clumped isotope bottom water temperature record data from Ocean Drilling Program (ODP) Site 747 (Leutert et al. in progress) - Leutert, Thomas; Modestou, Sevasti; Bernasconi, Stefano; Meckler, Nele (IEDA: EarthChem Library, 2021)
Abstract: This dataset contains D47, d18O and d13C data measured on middle Miocene benthic foraminifera from Ocean Drilling Program (ODP) Site 747. We provide replicate-level raw data to allow for data reprocessing. Other Description: Thomas J. Leutert, Sevasti Modestou, Stefano M. Bernasconi, A. Nele Meckler (in review), “Southern Ocean bottom water cooling and ice sheet expansion during the middle Miocene climate transition”, Climate of the Past